2014
DOI: 10.5505/tjb.2014.55477
|View full text |Cite
|
Sign up to set email alerts
|

Major Fatty Acids Composition of 32 Almond (Prunus dulcis (Mill.) D. A. Webb.) Genotypes Distributed in East and Southeast of Anatolia

Abstract: Major fatty acids composition of 32 almond (Prunus dulcis [Mill.] Hara and Radin (1978) method were used. Fatty acids content were determined using gas chromatographic (GC) analysis. The datas were evalulated with SPSS 17.0 statistical program. Results: In the gas chromatographic analysis, palmitic acid (16:0), palmitoleic acid (16:1), stearic acid (18:0), oleic acid (18:1), linoleic acid (18:2), and linolenic acid (18:3) were determined to be 5.34%, 0.70%, 0.85%, 74.46%, 17.89%, and 0.75% respectively. Sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
1
11
1
Order By: Relevance
“…Still higher oleic acid contents have been reported by Nanos et al (2002) (72-80%) and Kodad et al (2008) (69-78%) for domestically used kernels. Karatay et al (2014) reported that average palmitic, palmitoleic, stearic, oleic, linoleic and linolenic acid amounts of 32 almond oils were found 5.34%, 0.70%, 0.85%, 74.46%, 17.89% and 0.75%, respectively. Rabada ´n et al ( 2017) determined 5.87-7.64% palmitic, 0.54-0.86% palmitoleic, 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Still higher oleic acid contents have been reported by Nanos et al (2002) (72-80%) and Kodad et al (2008) (69-78%) for domestically used kernels. Karatay et al (2014) reported that average palmitic, palmitoleic, stearic, oleic, linoleic and linolenic acid amounts of 32 almond oils were found 5.34%, 0.70%, 0.85%, 74.46%, 17.89% and 0.75%, respectively. Rabada ´n et al ( 2017) determined 5.87-7.64% palmitic, 0.54-0.86% palmitoleic, 1.…”
Section: Resultsmentioning
confidence: 99%
“…The oleic acid content of some of the of almond species have been reported to be in between 66.7 and 69.7%, and the linoleic acid content has been detected in the range of 18.2-23.0% (Moayedi et al 2011). Karatay et al (2014) reported 74.46% oleic, 0.70% palmitoleic, 17.89% linoleic, 5.34% palmitic, 0.85% stearic and 0.75% linolenic acid as an average of a total of 32 different almond varieties. The presence of oleic (72.5-79.9%), linoleic (13.5-19.8%) and palmitic (5.9-6.7%) acids have been reported in different cultivars of almonds (O ¨zcan et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Present results of almonds were comparable with previous reported data of almond by Safa et al, [29] in Turkey showing 60.18 % of MUFA. Huseyin et al, [30] in 2014 also worked on different genotypes of almond and reported comparable limit of MUFA i.e. 61.80 g/100g.…”
Section: Fatty Acid Compositionmentioning
confidence: 97%
“…In general, fatty acids profiles of almond oil have shown high percentages of monounsaturated fatty acids and low content of unsaturated fatty acids [35]. Anyway, the composition of oils depends on origin, country and climatic conditions and even vary between different genotypes [13,18,19,21,22,34]. Sathe et al have shown that the most abundant fatty acids in almonds grown in California are oleic and linoleic acids, but the quantity depends on the location and the crop year [26].…”
Section: Introductionmentioning
confidence: 99%
“…As it can be observed, the highest concentration in any fatty acid in almond oil is oleic acid, a MUFA important in human consumption. In order to compare the fatty acid composition of almond oils obtained from different almond varieties grown in diverse parts of the world we used the data obtained in this study and that was reported in some papers[4,6,13,15,17,26,27,34]. These data are shown in TableII.TableII…”
mentioning
confidence: 99%